URGENSI PENYATUAN KALENDER HIJRIYAH GLOBAL - MUSYAFA', MUHAMMAD ALWI; Qulub, Siti Tatmainul (ELFALAKY: Jurnal Ilmu Falak, 2021)
Calendar is one of the most important tools in human civilization. For Muslims, the calendar has not only a social function, but also has a spiritual function. However, the Islamic civilization that has existed for centuries, does not have a synchronous calendar system yet, in the sense of one global date. This causes Muslims around the world not to be able to conduct religious celebrations simultaneously to celebrate any important moments such as Eid al-Fitr, Eid al-Adha, and fasting Ramadan. It is not easy to realize the unification of the global hijriyah calendar, because aspects of Syariah and astronomy must be studied carefully. At least there are several things that make the unification of the Hjriyah calendar urgent to do. First, realizing the unity and integrity of Muslims. Second, realizing the time’s unity of worship of Muslims. Third, at the global level, this unification of worship times is also beneficial for Muslims who reside in non-Muslim majority areas.